Absence of Chlamydia-like organisms in pigs. (September 2015) - Van Gils, M.; Aeby, S.; Vanrompay, D.; Greub, G.
Abstract: Porcine reproductive failure, especially abortion, causes significant economic loss in the pig industry. Waddlia chondrophila and Parachlamydia acanthamoebae are potential abortigenic agents for pigs. Therefore, we investigated the presence of these two Chlamydia -like organisms in abortion-related samples originating from Belgian pig farms. All investigated samples remained negative.